2017
DOI: 10.3171/2015.9.jns151311
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for cerebral arteriovenous malformations: evaluation of long-term outcomes in a multicenter cohort

Abstract: OBJECTIVE In this multicenter study, the authors reviewed the results following Gamma Knife radiosurgery (GKRS) of cerebral arteriovenous malformations (AVMs), determined predictors of outcome, and assessed predictive value of commonly used grading scales based upon this large cohort with long-term follow-up. METHODS Data from a cohort of 2236 patients undergoing GKRS for cerebral AVMs were compiled from the International Gamma Knife Research Foundation. Favorable outcome was defined as AVM obliteration and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
93
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 42 publications
13
93
6
Order By: Relevance
“…Ding et al reported hemorrhage rates of 1.6% in unruptured and 2.0% in ruptured BAVMs; pre-SRS embolization was not significantly associated with post-SRS hemorrhage 33 34. Starke et al reported an overall post-SRS hemorrhage rate of 1.1% 35. Kano et al reported annual rates of post-SRS hemorrhage of 5.5% during years 0–3 and 2.8% during years 3–6 17.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al reported hemorrhage rates of 1.6% in unruptured and 2.0% in ruptured BAVMs; pre-SRS embolization was not significantly associated with post-SRS hemorrhage 33 34. Starke et al reported an overall post-SRS hemorrhage rate of 1.1% 35. Kano et al reported annual rates of post-SRS hemorrhage of 5.5% during years 0–3 and 2.8% during years 3–6 17.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated risk of both initial and repeat hemorrhage for these deep-seated CCMs compared to cortical CCMs favors intervention, whereas the relatively high rate of neurological morbidity associated with surgical resection of these lesions supports a more conservative approach 41)42). Although radiosurgery is a conceptually attractive alternative to surgical resection of eloquent CCMs, the radiosurgery-induced complication rate is significantly higher for CCMs than for AVMs, and CCMs cannot be radiologically monitored for obliteration after radiosurgery 3)5)6)8)9)10)12)13)14)15)16)17)18)19)20)21)22)23)25)26)27)28)29)30)31)32)33)34)35)36)37)43)44)49)50)52)53)56)59)63)64)65)66)67)68). Instead, the proposed effect of radiosurgery on CCMs is a decreased risk of symptomatic hemorrhages, which is controversial due to temporal clustering of CCM hemorrhages 4).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, multicenter cohort studies and prospective registries, such as those conducted by the International Gamma Knife Research Foundation (IGKRF) and the AANS and ASTRO SRS registries, may yield more reliable findings than systematic reviews and meta-analyses. [3][4][5][6][7]20,[23][24][25] Adeel Ilyas, MD Phoenix, AZ 4 Taipei Veterans General Hospital, Taipei, Taiwan TO THE EDITOR: It was a great pleasure to read the article by Ilyas et al, 3 which pooled the data to compare the effects of volume-staged (VS) and dose-staged (DS) stereotactic radiosurgery (SRS) in patients with large brain arteriovenous malformations (AVMs) (Ilyas A, Chen CJ, Ding D, et al: Volume-staged versus dose-staged stereotactic radiosurgery outcomes for large brain arteriovenous malformations: a systematic review. J Neurosurg 128:154-164, January 2018).…”
Section: Responsementioning
confidence: 99%
“…Unfortunately, some degree of overlap is typically unavoidable in systematic reviews, where access to individual patient data is limited. 1,16,17,22,25 Furthermore, the degree of overlap cannot be fully quantified. Thus, the effects of including potentially overlapping articles on the results are difficult to predict.…”
Section: Responsementioning
confidence: 99%